Science Articles in "The Conversation Indonesia": Identifying Argumentative Patterns and Predicting Their Contribution to Science Journalism in Indonesia - Ana Nadhya Abrar; I Gusti Ngurah Putra; Adam Wijoyo Sukarno; Desmalinda Desmalinda; Mirfath Mirfath (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
In this paper, the authors investigate argument activities of the journalism of The Conversation Indonesia (TCID). Taking into consideration five elements of argumentation —philosophical component, theoretical component, empirical component, analytical component, and practical component—this study identifying patterns argument that characterize of 41 science articles in 2021 by using qualitative content analysis. To complete the data, we conducted in-depth interviews with the chief of editor/content director of TCID. We also conducted an extensive review of current literature. This paper finds that most of the science articles reported by TCID uses 3 component arguments, namely the philosophical component, the empirical component, and the practical component. This shows that the authors only have a degree of wanting to form knowledge at a moderate level. Other data shows not all writers present predictive arguments in themselves. Only 80% of authors present predictive arguments. We argue that science journalism practiced by TCID is not passionate about building knowledge among its readers. It has not succeeded in promoting Indonesian science journalism as a means of forming readers' knowledge. Therefore, strong efforts are needed to ensure that science journalism can ground research results that shape readers' knowledge.